REPRESENTASI ETIKA JAWA DAN PENDIDIKAN KARAKTER DALAM UPACARA ADAT CEPROTAN DI PACITAN: SEBUAH KAJIAN ETNOPEDAGOGI - Rizky Permatasari Permatasari; Rosy Tristanti; Kusmira Dwi Ayuani (Universitas Sebelas Maret, 2026)
This study aims to explore the representation of Javanese ethics and character education values in the Ceprotan traditional ceremony in Sekar Village, Pacitan, and relate them to the context of ethnopedagogy in Javanese language learning. The phenomenon of moral degradation in the era of globalization demands the revitalization of local wisdom as the basis for character building in students. This study uses a qualitative descriptive method with an ethnographic approach. Data were collected through participatory observation, in-depth interviews with traditional leaders, and documentation. Data analysis was conducted using the Miles & Huberman interactive model, which includes data condensation, data presentation, and conclusion drawing. The results show that the Ceprotan traditional ceremony contains fundamental Javanese ethical values, such as gratitude, harmony, respect, and unity of feeling. Ethnopedagogically, these values are represented in the symbolism of cengkir and ritual processes that teach mental toughness and social harmony. The implications of this research offer a framework for integrating local wisdom into Javanese language teaching materials as an effort to strengthen the Pancasila Student Profile, which is contextual and based on regional cultural identity.